Shaqra University's Role in Building the Mental Image of the Kingdom's Vision 2030 among Its Students (Journal Of Educational and Psychological Researches, 2022)
The study problem is about the role of Shaqra University in building the mental image of the Kingdom’s 2030 vision among its female students. The study aims to examine the university’s role in providing information about the Kingdom’s 2030 vision, its role in shaping the vision’s image, the university’s role in the behavioral aspect of the vision, along with studying the extent of differences in answers of the sample individuals towards the study themes attributed to the personal variables. The researcher adopted the descriptive survey method. A sample of (1399) female students was used to achieve the study objectives. The results showed that university’s role in building the mental image of the Kingdom’s 2030 vision, among its students in general, was mediocre from the sample’s point of view, for the three themes: providing information about the Kingdom’s vision 2030, forming the image of the Kingdom’s vision, and the university’s role in the behavioral aspect of the Kingdom’s vision 2030. It found also that there are no statistically significant differences between the study sample answers in terms of the three study themes, due to the number of academic years that have been spent at the university so far. There are no significant differences between the sample in the three study themes, depending on the faculty variable (scientific-practical). There are significant differences between the samples in the three study themes, depending on two variables: the extent to which the college assigns the sample to any work related to the Kingdom's vision 2030, and the acquisition of information through the study at the college about the Kingdom's 2030 vision.